Student's satisfaction on using student portal at Universiti Teknologi Malaysia, Skudai, Johor / Nur Farhana Harun - Harun, Nur Farhana (Faculty of Business and Management, 2013)
Student's portal plays an important role in every student's in Universiti Teknologi Malaysia, Skudai, Johor. It also increasingly being used for important task especially related about their academics matters. However, no researches that have proof the study on student's satisfaction or not. Therefore, this paper aimed to investigate the level of student's satisfaction on using student portal at Universiti Teknologi Malaysia, Skudai, Johor. Based on previous study, show that the system quality, service quality and information quality give impact to the student's satisfaction. The measurement is use by the framework is adapted from the Delone McLean framework in Portal Effec::veness. This research used questionnaire that were distributed to 110 students among Bachelor of Science Human Resource Development program and researchers were used SPSS version 18.0 to interpret the finding of this study.